Balance sheet analysis of joint stock companies listed on the Karachi stock exchange (Karachi : State Bank of Pakistan, 2006)
This analysis is based on the published balance sheets of non-financial companies listed at the Karachi Stock Exchange. For the purpose of comparison, the analysis of the five previous years is included in each years publication.
2001 - 2006
usc 29/11/2021
Ref.
Keywords: Pakistan